Gastrointestinal manifestations as early symptoms to diagnose COVID-19 paediatric cases - Robinson, J; Banerjee, I; Leclézio, A (Journal of Biomedical Sciences, 2021)
Background: The international situation surrounding the COVID-19 pandemic is seeing multiple countries battle various waves of the SARS-CoV-2 virus infections, with millions of individuals being infected globally. COVID-19 cases initially involved the immuno-compromised and elderly. As the virus has infected millions globally, the demographic profile of cases has shifted with more children being infected; this increase in younger individuals contracting the infection has resulted in new symptoms with altered manifestations and presentations of the disease in the young. In comparison to the severe symptoms of COVID-19 in adults children present with a more trivial group of symptoms. The majority of children develop mild symptoms or remain asymptomatic. This is in stark contrast to adults who have a higher admission rate with severe symptoms. A sign of great importance and now incidence in pediatric cases with COVID-19 is that of the gastrointestinal tract. The virus has a tropism for the GIT due to the presence of ACE2 receptors, which facilitate the entry of the virus into the cell. Conclusion: It is now established that the GIT symptoms form part of a newly recognized multisystem inflammatory syndrome (MIS-C) which occurs as a result and or manifestation of the COVID-19 infection. The innate difficulty in correctly and accurately diagnosing such a case is that the symptoms very close mimic gastroenteritis and acute abdominal pathologies. Therefore, physicians need to be aware of the various manners in which the COVID-19 infection manifests itself in children to diagnose better and isolate the cases.